Killing in pairs: radicalisation patterns of violent dyads - O'Connor, Francis (International journal of conflict and violence, 2018)
In recent years there has been an upsurge in violent attacks conducted by pairs of individuals who have undergone a shared process of radicalisation. Violent dyads remain a relatively understudied phenomenon. Using a relational approach, this article analyses the unique character of dyadic radicalisation and how it differs from instances of lone actor or group-based terrorism. It draws on a number of recent case studies, analysing instances of non-kin, fraternal, and spousal dyads. Its principal case study is a failed attack in Germany in 2006, based on a range of documentary sources as well as an interview with one of the perpetrators.